Scanning electrochemical microscopy - Bard, Allen J.; Mirkin, Michael V. (Boca Raton, Fla. : CRC Press, 2012)
"Scanning Electrochemical Microscopy (SECM) is an indispensable tool for the study of surface reactivity, and scientists are increasingly attracted to this method because of its simplicity of use and the quantitative results. The fast expansion of the SECM field during the last several years has been fueled by the introduction of new probes, commercially available instrumentation, and new practical applications. This book offers essential background and in-depth overviews of specific applications. This edition, thoroughly updated, retains original chapters and offers four new chapters covering applications that have emerged or expanded since the first edition's publication." --
"Preface During the 10 years that have passed since the publication of the first edition of this book, scanning electrochemical microscopy (SECM) has evolved substantially. The number of publications in this field has greatly increased, and their focus has changed from proof-of-concept experiments to realworld applications. SECM has been employed as an electrochemical tool to study heterogeneous and homogeneous reactions, for high-resolution imaging of various substrates, including biological cells, and for microfabrication. This technique is now used by a number of research groups in many different countries. We think the time has come for a new edition of this monograph, which would provide up-to-date comprehensive reviews of different aspects of SECM. All chapters in this edition are either new or thoroughly updated. Chapters 1 through 5 contain experimental and theoretical background, which is essential for everyone working in this field. Chapter 1 covers the principles of SECM measurements, Chapter 2 deals with instrumentation, Chapter 3 describes the preparation of SECM probes, Chapter 4 covers imaging methodologies, while Chapter 5 deals with theory. Other chapters are dedicated to specific applications and are self-contained. Although some knowledge of electrochemistry and physical chemistry is assumed, the key ideas discussed are at a level suitable for beginning graduate students. SECM has proved useful for a broad range of interdisciplinary research. Various applications discussed in this book range from studies of biological systems to sensors to probing reactions at the liquid-liquid interface"--
Includes bibliographical references and index.
Keywords: Scanning electrochemical microscopy; SCIENCE / Chemistry / Analytic; TECHNOLOGY & ENGINEERING / Material Science